Telehealth application of an ultrasonic home spirometer. Issue 8 (11th March 2022) - Doumit, Michael; Ledwos, Rianna; Plush, Leanne; Chuang, Sandra; Gray, Melinda; Jaffe, Adam; McBride, Jamie
Abstract : Objective: To investigate the validity and home use of a personal ultrasonic spirometer. Methods: Supervised spirometry was performed using laboratory equipment and a personal ultrasonic spirometer. In addition, the ability of children to perform acceptable spirometry during supervised telehealth appointments at home was assessed. Results: 59 children completed spirometry on both devices. There was high between-device intraclass correlation coefficient (ICC) for forced expiratory volume in 1 s (FEV1 ) and forced vital capacity (FVC): ICC 0.991 (95% CI 0.985 to 0.995) and 0.989 (95% CI 0.981 to 0.993), respectively. Bland-Altman analysis revealed mean bias and limits of agreement of −0.01 (−0.22 to 0.24) L for FEV1 and −0.02 (−0.30 to 0.33) L for FVC. 125 of 140 (89%) supervised telehealth spirometry sessions were acceptable. Conclusion: There was excellent reliability in between-device measurements; however, the limits of agreement were wide. Therefore, caution is needed if the device is used interchangeably with laboratory equipment. High success rates of telehealth spirometry sessions indicate the device is suitable for this application.